A brief review on piezoelectric PVDF nanofibers prepared by electrospinning. (4th April 2018) - Xin, Yi; Zhu, Jianfeng; Sun, Hongshuai; Xu, Yang; Liu, Tao; Qian, Chenghui
ABSTRACT: Poly(vinylidene fluoride) (PVDF) has been a kind of particularly attractive piezoelectric materials for its excellent piezoelectric property. It has been proven that the piezoelectric property of PVDF can be improved by electrospinning. Recently, the technical innovations on the multiple aspects of preparing electrospun PVDF nanofibers such as collecting equipment and the pretreatment emerged in endlessly. The article introduces electrospinning briefly firstly and the second part of the paper introduces some recent research on the preparation of electrospun PVDF nanofibers. The researches about promising applications using electrospun PVDF nanofibers involve biomedicine, sensors, and energy harvesting due to its flexibility, biocompatibility, and outstanding performance. The last part of the paper reviews the typical research.